2015
DOI: 10.1016/j.jallcom.2015.04.080
|View full text |Cite
|
Sign up to set email alerts
|

Atomic oxygen adsorption on 3.125 at.% Ga stabilized δ-Pu (1 1 1) surface

Abstract: a b s t r a c tAll-electron density functional theory was used to investigate atomic oxygen adsorption on a gallium stabilized d-plutonium (1 1 1) surface. High symmetry on-surface and interstitial adsorption sites, along with local environment (as determined by the absence or presence of gallium) were explored. The calculations comprised full structural relaxations. Spin-orbit-coupling was also taken into account to assess the complexity of absorbate-substrate interactions. We observed that O adsorbate prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 27 publications
4
25
1
Order By: Relevance
“…Additionally, the hydrogen atom prefers to interact much more strongly to the Pu atom than the Ga atom in the hydrogenvacancy complex [31]. The latter calculation results suggested that the presence of Ga in a Pu matrix could slow down the growth of Pu oxide layers [11], judged from the energetics of O atom at different sites (i.e., top of Ga, bridge between Pu and Ga, hollow sites, and interstitial site. ).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…Additionally, the hydrogen atom prefers to interact much more strongly to the Pu atom than the Ga atom in the hydrogenvacancy complex [31]. The latter calculation results suggested that the presence of Ga in a Pu matrix could slow down the growth of Pu oxide layers [11], judged from the energetics of O atom at different sites (i.e., top of Ga, bridge between Pu and Ga, hollow sites, and interstitial site. ).…”
Section: Introductionmentioning
confidence: 94%
“…The total energy of a free O atom is calculated by using a periodic cubic cell with a lattice constant of 15 Å and only one k point C in the framework of spin-polarized DFT. Moreover, pure spin-polarized DFT method is used to calculate the total energy of a-Ga crystallized in orthorhombic structure to obtain the energy of a Ga atom [11].…”
Section: Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have reported the adsorption of O on a 3.125 at. % Ga stabilized δ-Pu (111) [23], which showed that O preferred to be threefold coordinated in a Pu-environment and Ga does influence the electronic structure of the nearest 5 neighboring Pu atoms. In this paper we selected a higher concentration of Ga within a δ-Pu (111) matrix.…”
Section: Introductionmentioning
confidence: 97%